Age as a moderating factor of treatment resistance in depression. Issue 1 (20th April 2023) - Kautzky, Alexander; Bartova, Lucie; Fugger, Gernot; Dold, Markus; Souery, Daniel; Montgomery, Stuart; Zohar, Joseph; Mendlewicz, Julien; Fabbri, Chiara; Serretti, Alessandro; Rujescu, Dan; Kasper, Siegfried
Abstract: Background: Treatment-resistant depression (TRD) is an important clinical challenge and may present differently between age groups. Methods: A total of 893 depressed patients recruited within the framework of the European research consortium "Group for the Studies of Resistant Depression" were assessed by generalized linear models regarding age effects (both as numerical and factorial predictors) on treatment outcome, number of lifetime depressive episodes, hospitalization time, and duration of the current episode. Effects of age as numerical predictor on the severity of common depressive symptoms, measured with Montgomery–Åsberg Depression Rating Scale (MADRS) for two-time points, were assessed by linear mixed models, respectively, for patients showing TRD and treatment response. A corrected p threshold of 0.001 was applied. Results: Overall symptom load reflected by MADRS ( p  < 0.0001) and lifetime hospitalization time ( p  < 0.0001) increased with age in TRD patients but not treatment responders. In TRD, higher age was predicting symptom severity of inner tension, reduced appetite, concentrations difficulties, and lassitude (all p  ≤ 0.001). Regarding clinical significance, older TRD patients were more likely to report severe symptoms (item score > 4) for these items both before and after treatment (all p  ≤ 0.001). Conclusions: In this naturalistic sample of severely ill depressed patients, antidepressant treatment protocols were equally effective in addressing TRD in old age. However, specific symptoms such as sadness, appetite, and concentration showed an age-dependent presentation, impacting residual symptoms in severely affected TRD patients and calling for a precision approach by a better integration of age profiles in treatment recommendations.